PENGARUH LEG PRESS TERHADAP PENINGKATAN KEKUATAN TUNGKAI KAKI ATLET TAEKWONDO DOJANG PPO KUPANG - Koroh, Elron Apriel; Runesi, Salmon; Martin Siahaan, Jurdan (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2024)
Consists of three words, namely Tae, kwon and do. Tae means feet or crushing with the feet. So, if interpreted simply, a good kicking technique in the martial sport of taekwondo is influenced by the position of the feet, body balance, waist and angle when lifting the knees, so that you can get a hard and right-on-target explosion. This research method uses a quantitative method based on the philosophy of positivism, used to research certain populations or samples, data collection using research instruments, quantitative/statistical data analysis, with the aim of testing predetermined hypotheses. The results of the t-test can be concluded that the comparison of the results of the Leg Muscle Strength training of Taekwondo Dojang PPO Kupang City Athletes after training obtained a t-test value that was greater than before training with a calculated t value of 5.06 at a = 5% with db = 11 -1 =10 to get t(0.975)(10)=2.18 Based on the results of research data calculations and discussions, it is known that there is an influence, so the conclusions that can be drawn are as follows: There is an influence of leg press training to increase the leg muscle strength of Taekwondo Dojang PPO Kupang City athletes. Based on the t-test above, it can be concluded that the results of the comparison test of leg press training to increase the leg muscle strength of Taekwondo athletes' legs, this means that weight training using the leg press gives better results than without using the leg press.